Too Much, Too Little, or the Wrong Kind of 'Theory' in the Study of Religions? - Kavanagh, Christopher M. (Method & theory in the study of religion, 2018)
In response to the recent publication of Theory In a Time of Excess this article offers an outsider perspective on the theoretical issues raised and why they are ultimately unlikely to be resolved. The article argues that there is a widespread problematic tendency to equate theory with a specific category of critical theory that tautologically restricts the theoretical boundaries of the study of religion field and neglects the contributions of more empirically inclined theorists. In a similar manner, essentialising narratives about the Cognitive Science of Religion that portray the field as unified and monolithic are highlighted and the validity of such critiques is questioned.